Electrospun nanofibrous poly (Lactic Acid)/Titanium dioxide nanocomposite membranes for cutaneous scar minimization - Marsi, Teresa C. O. (2019)
The animal study was reviewed and approved by 10/2015-CEUA/ICT/CJSC-UNESP.